Effectiveness of Copyright Registration for Book Works for Publishers to Obtain Legal Protection: Efektivitas Pendaftaran Hak Cipta Hasil Karya Buku Bagi Penerbit untuk Mendapatkan Perlindungan Hukum - Bagus Bintara Putra (Universitas Negeri Semarang, 2012)
Copyright registration according to the explanation of Article 35, Paragraph (4) of Act No. 19 of 2002 on copyright is basically is a must for the creator or the copyright holder. CV Range Science, PT. Yudhistira Ghalia Indonesia, PT Bumi Revised is a company engaged in the field of book publishing. How does the question arise the effectiveness of registration of Copyright works made by the book publisher to get legal protection. Draft issue in this research: 1) how effectiveness registration copyright against masterpiece book for the issuer to shelter law? 2) obstacles are emerging for registration copyright masterpiece book published by publishers book? 3) how efforts to overcome impediments in registration copyright masterpiece book published by publishers book? This research using methods approach juridical empirical, using data primary and secondary data then analyzed by using analysis of data qualitative. The results of this research is the copyright registration is considered effective to protect the work of book published by the Publisher, obstructions in the copyright registration is only contained in the registration system did not make substantial examination on works that are listed, as well as the life span of the registration process and the completion of the copyright issues, according to the Publisher, an effort that can be done to overcome the barriers of copyright registration is predicated on the liveliness of the author or copyright holder. Conclusion of this research is to 1) Copyright Registration for works of the book by the Publisher is quite effective to provide the legal protection of copyright of works published book. 2) Barriers in the copyright registration comes as Indonesia has a declarative protection does not know specifically delegated substantive examination on the registration process. 3) efforts to overcome the obstacles it is by the applicants must be more active, quick and precise on the process of copyright registration. Advice of this research is 1) requires rules governing more particularly on the copyright, 2) the issuer shall register copyright masterpiece they published for more law, shelter 3) and optimization requires badan agency that oversees against violations of copyright, 4) people need of consciousness of users to use the book published by the original issuer.